Strategies and recommendations for Nigerian rural development, 1969/1985 - Johnson, G.L. (East Lansing, Mich. : Consortium for the Study of Nigerian Rural Development, 1969)
This report contains CSNRD's preliminary recommendations to further the development of Nigerian agriculture with projections of the effects of alternative courses of action over the 1970 - 85 period.
A consortium for the study of Nigerian rural development in agriculture for production and research programs
Bibliography: p. 151-154.
sju 22/10/2019
Arch
Keywords: Rural development; Agriculture; Agriculture and state; Nigeria